A review: The utilization and its benefits of liquid smoke from lignocellulosic waste. Issue 1 (November 2021) - Winarni, I; Gusmailina,; Komarayati, S
Abstract: In the integrated charcoal technology, the smoke arising from the process is flowed into a pipe which is cooled, so that the smoke turns into a liquid, so it is called liquid smoke. Therefore, the technology to produce liquid smoke is environmentally friendly. The raw material used in the process of making wood vinegar is generally in the form of lignocellulose waste which contains lignin and cellulose such as wood waste, bamboo waste, oil palm shell waste, coconut shell waste and others. With simple technology input, liquid smoke can be produced from this waste, which has many benefits. The method to produce the liquid smoke was through a process of charcoal or pyrolysis which produces three forms of solid products, namely charcoal, products in the form of gases, namely smoke, and products in the form of liquids, so called tar and liquid smoke; and the main component as a characteristic of liquid smoke were acetic acid, phenolic and carbamic acid. Phenol is the compound that plays the most role in liquid smoke, because it is antibacterial and antifungal and inhibits fat oxidation. Therefore, liquid smoke with its various benefits can be a solution for the problems of pets and bacteria in agriculture or environmental pollution.